The controller's function : the work of the managerial accountant - Bragg, Steven M.; Roehl-Anderson, Janice M. (Hoboken, N.J. : Wiley, 2011)
"This book provides an overview of the functions and responsibilities of the controller/management accountant in a corporation. A controller is the chief accounting executive of a corporation whose chief responsibilities include: (1) planning and control (i.e., budgeting), (2) financial reporting and interpreting, (3) tax administration, (4) management audits and development of accounting systems, and (5) internal/IT audits. Topics covered in this book include: Job description for all positions reporting to the controller. Flex budgeting. Discussion of sales bottlenecks. Role of throughput in determining appropriate overhead levels. Throughput analysis for capital investments. Discussion of the fast close for public companies. Discussion of cost reduction and analysis. Cost Accounting. Accounting for acquisitions."--
The Controller's Function: The Work of the Managerial Accountant; Contents; Preface; 1 The Controller's Job; MAIN JOB FUNCTIONS; JOB DESCRIPTION; JOB QUALIFICATIONS; ORGANIZATIONAL STRUCTURE OF THE ACCOUNTING DEPARTMENT; ETHICS; 2 Internal Control; BASIC ELEMENTS; CONTROLS TO USE IN YOUR BUSINESS; ELEMENTS OF INTERNAL ACCOUNTING CONTROL; LEVELS OF CONTROLS; FRAUD; AUDITING FOR FRAUD; NOTES; 3 Planning and the Strategic Plan; STRATEGIC PLAN OVERVIEW; SYSTEM OF PLANS; PLANNING CYCLE; PLANNING ROLES; PLANNING TIMING AND THE PLANNING PERIOD; BUSINESS MISSION; DEVELOPING LONG-RANGE OBJECTIVES.
Revised edition of: The controller's function / Janice Roehl-Anderson, Steven M. Bragg. 3rd ed.
Includes index.
Print version record.
Keywords: Managerial accounting; Controllership; Auditing; Budget in business; Auditing; Budget in business; Controllership; Managerial accounting; BUSINESS & ECONOMICS -- Accounting -- Managerial; Auditing; Budget in business; Controllership; Managerial accounting; Electronic books; Electronic books